Effect of Adding NAA and BAP on the Growth of Kepok Kuning Banana (Musa paradisiaca L.) Planlet on MS Media in Vitro - Andany, Charizma; Ratnasari, Evie (LenteraBio : Berkala Ilmiah Biologi, 2023)
The availability of Kepok Kuning Banana (Musa paradisiaca L.) seeds is increasingly limited due to physiological diseases such as leaf wilt. Therefore, tissue culture techniques were carried out as a solution for propagating Kepok Kuning banana seeds which disease free. This study's purpose is to determine the effect of adding NAA and BAP to MS media in vitro on the growth of Kepok Kuning Banana plantlets. This study used a completely randomized design with one treatment factor, the combination of NAA and BAP concentrations with five treatments; A (4ppm NAA + 8ppm BAP), B (5ppm NAA + 7ppm BAP), C (6ppm NAA + 6ppm BAP), D (7ppm NAA + 5ppm BAP), E (8ppm NAA + 4ppm BAP). Plantlet growth data including number of shoots, leaves, roots, and plantlet height were analyzed using one-way ANOVA test followed by Duncan's test at 5% level. The results showed that the addition of NAA and BAP affected the growth of Kepok Kuning banana plantlets on MS media in vitro. This is shown in the optimal number of shoots and leaves in treatment A, treatment B, and treatment C. Meanwhile, the number of roots and plantlet height is optimal in treatment D, and treatment E.